2020
DOI: 10.1038/s41598-020-74159-w
|View full text |Cite
|
Sign up to set email alerts
|

A novel serine protease inhibitor as potential treatment for dry eye syndrome and ocular inflammation

Abstract: Dry eye syndrome (DES), a multifactorial disorder which leads to ocular discomfort, visual disturbance and tear film instability, has a rising prevalence and limited treatment options. In this study, a newly developed trypsin-like serine protease inhibitor (UAMC-00050) in a tear drop formulation was evaluated to treat ocular inflammation. A surgical animal model of dry eye was employed to investigate the potential of UAMC-00050 on dry eye pathology. Animals treated with UAMC-00050 displayed a significant reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 49 publications
0
27
0
2
Order By: Relevance
“…In a recent study, the serine protease inhibitor UAMC-00050 was evaluated in an in vivo model of DED. 46 UAMC-00050, a small diphenyl phosphonate with a multi-target inhibition profile, 47 , 48 was administered as eye drops in rats subjected to the removal of the exorbital lacrimal gland. UAMC-00050 induced a significant reduction in ocular surface damage, a decrement of IL-1α and TNF-α levels in tear fluid, although it did not exert any effect on tear volume.…”
Section: Novel Emerging Therapies For Ded With Anti-inflammatory Propmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, the serine protease inhibitor UAMC-00050 was evaluated in an in vivo model of DED. 46 UAMC-00050, a small diphenyl phosphonate with a multi-target inhibition profile, 47 , 48 was administered as eye drops in rats subjected to the removal of the exorbital lacrimal gland. UAMC-00050 induced a significant reduction in ocular surface damage, a decrement of IL-1α and TNF-α levels in tear fluid, although it did not exert any effect on tear volume.…”
Section: Novel Emerging Therapies For Ded With Anti-inflammatory Propmentioning
confidence: 99%
“…In addition, UAMC-00050 caused diminished inflammatory cell infiltration in the palpebral conjunctiva; in particular, both CD3 + and CD45 + cell were reduced in UAMC-00050 (5 mM)-treated animals in comparison to vehicle-treated and untreated animals. 46 To date, no clinical trials have been performed to evaluate the effects of UAMC-00050 in individuals with DED.…”
Section: Novel Emerging Therapies For Ded With Anti-inflammatory Propmentioning
confidence: 99%
“…A method to influence the protease signaling pathways is to directly alter protease activity by using selective inhibitors ( Vergnolle, 2016 ). In this respect, we previously developed selective serine protease inhibitors (patents WO/2007/045496, WO/2017/198753) ( Joossens et al, 2007 ) and recently showed their in vivo therapeutic potential in inflammation-induced visceral hypersensitivity ( Ceuleers et al, 2018 ; Hanning et al, 2021b ) and dry eye derived ocular inflammation ( Joossen et al, 2020 ). Besides, UAMC-00050 displays a favorable inhibitory profile with a good inhibition of the serine protease tryptase, together with a limited inhibition of proteases involved in the coagulation cascade ( Ceuleers et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…18 Recently, a new biologically active a-aminophosphonate (UAMC-00050) was developed at the University of Antwerp. [19][20][21] This diarylphosphonate shows good inhibitory activity against urokinase plasminogen activator (uPA), an enzyme involved in several physiological processes, such as tissue remodeling. 22 uPA can be also involved in the development of different diseases, for example, thrombolytic disorder, 23 cancer, 24 and eye diseases.…”
mentioning
confidence: 99%
“…25 UAMC-00050 is currently under investigation for the treatment of irritable bowel syndrome 26 and dry eye disease. 21 The key step of the synthesis of UAMC-00050, proposed by Joossens et al, 19,21 involves Birum-Oleksyszyn reaction, catalyzed by Cu(OTf) 2 in acetonitrile, which, on a small scale, provides 20% yield of the product (Scheme 1). In current work, a new catalyst has been introduced for the Birum-Oleksyszyn reaction.…”
mentioning
confidence: 99%